Pelatihan Office Visio Untuk Pembelajaran di Sekolah Menengah Kejuruan Penerbangan Dhirgantara Curug – Tangerang - Yayuk Suprihartini; Taryana Taryana; Elvi Amir; Rini Sadiatmi; Rubby Soebiantoro (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
Computer technology is very helpful for human tasks and has become an important need in everyday life. Computer technology has developed so rapidly that each student have to master it to make reporting easier.one of the programs software from windows is Microsoft office visio to create various diagrams such as flowcharts, block diagrams and data flow diagrams quickly for various reports. various diagrams such as flowcharts, block diagrams and data flow diagrams quickly for various reports.. So it is necessary to equip these students with the Visio program. This is the background to the need for Community Service with the title